Embryogenesis and plant regeneration from ovary derived callus cultures of ginger (Zingiber officinale Rose.) - RATNAMBAL, P N RAVINDRAN, K NIRMAL BABU, K SAMSUDEEN, M J (Journal of Spices and Aromatic Crops, 1996)
Ovary explants from 1-2 week old flowers of ginger (Zingiber officinale) developed profuse callus in Murashige and Skoog medium supplemented either with 2,4-dichlorophenoxyacetic acid (1 mgl-1) alone or with 2,4-dichlorophenoxyacetic acid (0.5 mgl-1) and benzyladenine (1 mgl-1). The callus later turned embryogenic and produced white globular embryoid like structures when cultured on modified Murashige and Skoog medium supplemented with benzyl adenine (10 mgl-1) and 2,4-dichlorophenoxyacetic acid (0.2 mgl-1). The embroyoid formation was more pronounced when growth regulators were removed from the culture medium after initial embryogenesis. Some of the embryoids developed into complete plantlets. The primary embryoids directly produced secondary embryoids in subsequent cultures on growth regulator free medium. The individual embryoids developed into plantlets with better rooting when a-naphthalene acetic acid (1 mgl-1) was added to the culture medium. About 80 per cent of these plantlets were established in soil.